LEADERSHIP QUALITIES AMONG THE B.ED. STUDENT TEACHERS IN COIMBATORE DISTRICT - Brindarani, V.; Geetha, D. (International Journal of Research -GRANTHAALAYAH, 2018)
Education is to improve humanity. Man becomes wise man through education. Education is a powerful instrument of social, economic and cultural transformation necessary for the realization of national goals. Leadership quality is considered as quality an integral part of the teacher education. Leader is one who makes his subordinate to do willingly what he wants. The efforts of subordinates are to be canalized in the right direction. As leaders, they are not only responsible for directing their subordinates but also responsible for the attainment of goals of education. One of the major objective of this study is to investigate Leadership Qualities among B.Ed., Student Teachers based on Gender, Religion, Types of Family, Medium of Study and Educational Qualification of Parents. The Sample 300 B.Ed., Student teachers from 10 colleges in Coimbatore District.